Bayesian Networks-based Shield TBM Risk Management System: Methodology Development and Application - Chung, Heeyoung; Lee, In-Mo; Jung, Jee-Hee; Park, Jeongjun (KSCE journal of civil engineering, 2019)
A risk management methodology that can be applicable to a shield Tunnel Boring Machine (TBM) tunneling project is proposed in this paper. A Shield TBM Risk Analysis Model (STRAM) is developed based on Bayesian networks. STRAM considers geological risk factors and TBM types, such as Earth Pressure Balance (EPB) open mode, EPB closed mode, and slurry TBMs, and systematically identifies the potential risk events that may occur during tunnel construction. It can also quantitatively evaluate the degree of risk for the identified potential risk events by estimating the cost of countermeasures against event occurrence. The proposed methodology based on STRAM can minimize the drawbacks of the TBM tunneling method, including difficulty in substituting the machine type once it is selected and excessive delay of the project due to unexpected risk events.